PENERAPAN MESIN PENGIRIS SINGKONG PADA INDUSTRI KECIL KRIPIK SINGKONG - Suriadi, IG.A.K.; Subagia, I D. G. A.; Atmika, I K. A. (Buletin Udayana Mengabdi; Vol 15 No 2 (2016): Jurnal Udayana Mengabdi, 2016)
The Negara city is an area that has already quite crowded, shown by the availability of many facilities, so small industrial/business group are emerging, one of which is an industry or group of enterprises manufacture of cassava chips "Niki Suka". Meanwhile, in the eastern region of of Bali island, there are UD. Gurih Sari, is a small industry that produces cassava chips as well . Production of chips is still utilizing local resources andproduced conventionally. UD Gurih Sari and Suka Niki Suka business groups, both have a similar problem that is related to productivity, caused by small capacity and conventional of cassava cutlery/slicer, as well as low educational background of human resources (HR). The aims of the activity is to generate cassava slicing/cutting machine. Solutions or methods offered in this program is to replace the equipment or the conventional way with a cassava mower/slicer. Technical planning activities of our team was using some input from business groups partner. The next activity in introducing the good management "of the company " that was dealed and desired by the partner. Then continued by the introcudtion of work safety. The first community service activities held on August 22, 2015 at Niki Suka women business group, located in the village Cupel, Negara, Jembrana District, Bali. The activities began with a demo making cassava chips conventionally by Niki Suka women business group, continued by introducing and demonstrating the machine that we made. This training can improve the skills of the workforce in producing cassava chips.
Keywords: Cassava chips, conventional, cutting efficiency, productivity